The effect of implant linking and ligament integrity on humeral loading of a convertible total elbow arthroplasty. (February 2019) - Brownhill, James R; Pollock, J Whitcomb; Ferreira, Louis M; Johnson, James A; King, Graham JW
Background: Both unlinked and linked total elbow arthroplasty (TEA) implants have been employed with no consensus as to the optimal design. The present study aimed to evaluate the effect of collateral ligament integrity and implant linkage on wear-inducing loads in a convertible TEA. Methods: Eight fresh frozen upper extremities were tested in an elbow motion simulator. A convertible TEA with an instrumented humeral stem was inserted using computer navigation. Elbow kinematics and humeral loading were recorded with the TEA both linked and unlinked. The collateral ligaments were then sectioned and testing was repeated. Results: In the dependent position, there was no effect of implant linkage or ligament sectioning on humeral loading. Humeral loading was significantly greater following sectioning of the collateral ligaments but not after linking the TEA with the arm in the valgus position. Humeral loading was significantly greater after linking the TEA but not after sectioning of the collateral ligaments and with the arm in the varus position. Conclusions: Collateral ligament integrity reduces wear-inducing loads for both an unlinked and linked TEA. Linkage of a convertible TEA increases humeral loading, which may have detrimental effects on implant longevity.